The critical role of pancreatic stone protein/regenerating protein in sepsis-related multiorgan failure - Hu, Ping; Lu, Yuan hua; Deng, Wei; Li, Qi; Zhao, Ning; Shao, Qiang; Wu, Ling; Wang, Xu zhen; Qian, Ke jian; Liu, Fen (Frontiers in Medicine, 2023)
Introduction: Multiple organ dysfunction syndrome (MODS) is common in patients with sepsistic admitted to an intensive care unit (ICU) and greatly increases mortality. Pancreatic stone protein/regenerating protein (PSP/Reg) is a type of C-type lectin protein that is overexpressed during sepsis. This study aimed to evaluate the potential involvement of PSP/Reg in MODS development in patients with sepsis. Methods: The relationship between circulating PSP/Reg levels, patient prognosis, and progression to MODS was analyzed in patients with sepsis admitted to the ICU of a general tertiary hospital. Furthermore, to examine the potential involvement of PSP/Reg in sepsis-induced MODS, a septic mouse model was established per the cecal ligation and puncture procedure, randomized into three groups, and subjected to a caudal vein injection of recombinant PSP/Reg at two different doses and phosphate-buffered saline. Survival analyses and disease severity scoring were performed to evaluate the survival status of the mice; enzyme-linked immunosorbent assays were performed to detect the levels of inflammatory factors and organ-damage markers in murine peripheral blood; terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining was performed to measure apoptosis levels in lung, heart, liver, and kidney tissue sections and to visualize the degree of organ damage in the mouse model; myeloperoxidase activity assay, immunofluorescence staining, and flow cytometry were performed to detect neutrophil infiltration levels in vital murine organs and the activation indexes of neutrophils. Results and discussion: Our findings indicated that Circulating PSP/Reg levels were correlated with patient prognosis and sequential organ failure assessment scores. Furthermore, PSP/Reg administration increased disease severity scores, shortened survival time, increased the TUNEL-positive staining rate, and increased the levels of inflammatory factors, organ-damage markers, and neutrophil infiltration in the organs. Neutrophils can be activated by PSP/Reg to an inflammatory state, both in vivo and in vitro, which is characterized by the increased levels of intercellular adhesion molecule 1 and CD29. Conclusions: Patient prognosis and progression to MODS can be visualized by monitoring PSP/Reg levels upon ICU admission. Additionally, PSP/Reg administration in animal models exacerbates the inflammatory response and severity of multiorgan damage, which may be accomplished by promoting the inflammatory state of neutrophils.